Psychometric Properties of Turkish Version of Pediatric Daytime Sleepiness Scale (PDSS-T) - Murat Bektas, PhD, RN; Ilknur Bektas, MSc, RN; Dijle Ayar, MSc, RN; Yasemin Selekoglu, RN; Ugur Ayar, BSN; Aslı Akdeniz Kudubes, MSc, RN; Sema Sal Altan, RN; Merry Armstrong, PhD, RN (Elsevier, 2016)
Purpose: The aim of the research was to evaluate the psychometric properties of the Pediatric Daytime Sleepiness Scale-Turkish Version (PDSS-T). Methods: The researchers chose a study sample of 522 grade 5-11 students. Data were collected using a demographic data collection form and the PDSS-T. Results: Cronbach α for the scale was .79 and Kaiser-Meyer-Olkin coefficient was .78. Item-total correlations for the scale varied between .53 and .73 (p < .001). The indices of model fit were determined to be the root mean square error of approximation at .07, the goodness of fit index at .97, and the comparative fit index at .97. Conclusions: The study's results showed that PDSS-T is a valid and reliable instrument for detecting Turkish-speaking children's and adolescents' daytime sleepiness. PDSS-T is convenient for professionals to prevent and manage daytime sleepiness.